Effects of increasing pantothenic acid on growth performance of segregated early-weaned pigs - G S Grinstead; R Stott; Robert D Goodband; Jim L Nelssen; Michael D Tokach; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1998)
We conducted a 28-d experiment to evaluate effects of increasing dietary pantothenic acid on growth performance of segregated early-weaned pigs. Pigs (initially 8.8 ± 2.21b and 11 ± 2 d of age) were fed a control diet (no added pantothenic acid) or the control diet with 30, 60, and 120 ppm of added pantothenic acid. Increasing pantothenic acid increased ADG and ADFI linearly from dO to 14 after weaning. However, from d 14 to 28 after weaning, pigs fed 60 mg/kg of added pantothenic acid tended to have the greatest ADG and ADFI. For the cumulative period (d 0to 28 after weaning), ADO and ADFI increased linearly with increasing added pantothenic acid. The linear improvements in weanling pig growth performance observed with increasing pantothenic acid indicated that current NRC (1998) requirement estimates may be too low. Because of the wide range of pantothenic acid concentrations used in our study, additional research is warranted to define a more precise requirement estimate.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Starter pigs; Pantothenic acid; Performance